THE ROLE OF INTERETHNIC HARMONY IN THE SOCIO-POLITICAL DEVELOPMENT OF UZBEKISTAN - Davlatova Saodat Tilovberdiyevna (International Journal of Literature and Language Studies, 2026)
This article explores the role of interethnic harmony in the socio-political development of Uzbekistan. It highlights how peaceful coexistence among more than 130 ethnic groups contributes to political stability, social cohesion, and sustainable development. Using a qualitative and analytical approach, the study examines demographic structure, state policy, and socio-economic indicators related to ethnic relations. The findings show that interethnic harmony in Uzbekistan is a key stabilizing factor that strengthens national unity, reduces social tensions, and supports economic progress. The research concludes that maintaining ethnic harmony is essential for long-term development and modernization of the country.